2014
DOI: 10.1103/physreva.90.033827
|View full text |Cite
|
Sign up to set email alerts
|

Superluminal two-color light in a multiple Raman gain medium

Abstract: We investigate theoretically the formation of two-component light with superluminal group velocity in a medium controlled by four Raman pump fields. In such an optical scheme only a particular combination of the probe fields is coupled to the matter and exhibits superluminal propagation; the orthogonal combination is uncoupled. The individual probe fields do not have a definite group velocity in the medium. Calculations demonstrate that this superluminal component experiences an envelope advancement in the med… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The magnetic sublevel 6S 1/2 , |F = 4, m = −2 corresponds to the level Y . Also, the levels 5P 3/2 , |F = 4, m = −3 and 6P 1/2 , |F = 4, m = −3 are excited levels U 1 and U 2 , respectively [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic sublevel 6S 1/2 , |F = 4, m = −2 corresponds to the level Y . Also, the levels 5P 3/2 , |F = 4, m = −3 and 6P 1/2 , |F = 4, m = −3 are excited levels U 1 and U 2 , respectively [41].…”
Section: Discussionmentioning
confidence: 99%
“…Yet such a superluminal propagation is hardly observed due to losses [35]. Some novel approaches have been proposed to utilize transparent spectral regions for fast light [37][38][39][40][41]. Specifically, it was shown that a linear anomalous dispersion can be created in a Raman gain doublet and therefore distorsionless pulse propagation is possible [38].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier theoretical studies for the localization mostly consider one-dimensional (1D) atom localization based on the atomic coherence and quantum interference effects [8][9][10][11][12]. Note that the quantum coherence and interference play a fundamental role in many other phenomena of atomic physics * hamid.hamedi@tfai.vu.lt † gediminas.juzeliunas@tfai.vu.lt and quantum optics, such as an electromagnetically induced transparency (EIT) [13][14][15][16][17][18], superluminal light propagation [19][20][21][22], optical bistability [23,24], Kerr nonlinearity [25,26], and others [27][28][29]. More recently, some schemes have been put forward for two-dimensional (2D) atom localization [30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum coherence and interference are two appealing phenomena which can lead to many interesting linear and nonlinear optical properties such as superluminal light propagation [1], optical bistability and Kerr nonlinearity [2][3][4][5][6][7][8][9][10], electromagnetically induced transparency (EIT) [11,12], four-wave mixing (FWM) [13][14][15], optical solitons [16,17], atom localization [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] etc.…”
Section: Introductionmentioning
confidence: 99%